2020
DOI: 10.3389/fpsyg.2020.535489
|View full text |Cite
|
Sign up to set email alerts
|

Social Exclusion and Green Consumption: A Costly Signaling Approach

Abstract: This article is dedicated to examine the impact of social exclusion (i.e., being rejected, isolated, excluded or ignored by other individuals or groups in society) on consumers’ intention of green consumption. Based on Costly Signaling Theory, three experiments have been conducted to explore one main effect and the corresponding mechanism together with two boundary conditions. Specifically, the first study tests the main effect and internal mechanism by manipulating the state of social exclusion. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 47 publications
(62 reference statements)
0
21
5
Order By: Relevance
“…Most of the existing research also focuses on the influencing factors and driving mechanisms of green consumption behavior. Guo (2020) examined the impact of social exclusion (i.e., being rejected, isolated, excluded, or ignored by other individuals or groups in society) on consumers' intention to consume green [10]. Ge (2020) explains the internal influence mechanism between social norm conflict and green consumption [11].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the existing research also focuses on the influencing factors and driving mechanisms of green consumption behavior. Guo (2020) examined the impact of social exclusion (i.e., being rejected, isolated, excluded, or ignored by other individuals or groups in society) on consumers' intention to consume green [10]. Ge (2020) explains the internal influence mechanism between social norm conflict and green consumption [11].…”
Section: Introductionmentioning
confidence: 99%
“…Yet research on whether ostracized individuals show more behavior for the greater good provides mixed results, with some studies showing negative (Li et al, 2020), some showing positive associations (Poon et al, 2015) of ostracism and pro-environmental behavior. Others showed positive associations of ostracism and proenvironmental behavior only when the pro-environmental behavior could be seen by others, thereby giving individuals the possibility to signal pro-sociality and increase the likelihood of future interactions with others (Guo et al, 2020).…”
Section: 3mentioning
confidence: 99%
“…The paradox is evidenced by the conflicting findings reported in the empirical studies. For example, Guo, et al [ 47 ] demonstrated that the socially excluded consumers are motivated to engage with green consumption as a prosocial behaviour to win social recognition. Lonely consumers are found to prefer ordinary products endorsed by the majority rather than distinct products [ 48 ].…”
Section: Lonely Consumers: Psychological Commercial and Social Immentioning
confidence: 99%
“… Self-affirmation; Green consumption; Prosocial behaviour; Product selection; Distinctive and popular products Commercial implications Gentina, Shrum and Lowrey [ 39 ] Loneliness leads to passive and active coping strategies associated with different types of materialism, which increases or decreases unethical behaviours among young consumers Materialism; Unethical behaviours Psychological implications Goodwin and Lockshin [ 27 ] The concept of solo shoppers is proposed and differentiated from lonely shoppers. Solo shopper; Stereotypes Commercial implications Guèvremont and Grohmann [ 70 ] Socially excluded consumers are more emotionally attached to authentic brand in seeking for belongingness Brand; Attachment to nonhuman; Self-affirmation Commercial implications Guo, Zhang, Liao and Wu [ 47 ] Socially excluded consumers engage with green consumption as a signal to gain social inclusion. Green consumption; Prosocial behaviour; Costly signalling; Self-sacrifice Commercial implications Hart and Royne [ 65 ] Loneliness enhances consumers’ responses to anthropomorphism appeals in the case of advertising messages, leading to a more positive attitude toward the brand Anthropomorphism; Brand; Persuasion Commercial implications Her and Seo [ 2 ] Anticipated loneliness reduces consumers’ intention to dine alone in public restaurant.…”
mentioning
confidence: 99%